Implementasi Kebijakan UU No 4 Tahun 2009 Terhadap Tambang Batubara Ilegal di Kalimantan Timur - Hasibuan, Juni Rahmad (Fakultas Hukum Universitas Balikpapan, 2025)
Coal mining in East Kalimantan is a strategic sector that contributes significantly to the regional economy; however, the practice of illegal coal mining (PETI) continues to proliferate in large numbers. Based on data from JATAM and research findings, there are more than 160 illegal mining sites spread across several districts and cities. These activities violate the provisions of Law No. 4 of 2009 on Mineral and Coal Mining, particularly Articles 37, 38, 75, and 158, which regulate mining permits (IUP, IUPK, IPR) and criminal sanctions. The analysis shows that economic factors (community dependence on instant employment opportunities), legal factors (weak law enforcement, overlapping authorities, and the lack of deterrent effect), and limited supervision are the main drivers behind the proliferation of PETI. The resulting impacts include environmental pollution (water, soil, and air), landscape degradation, loss of biodiversity, and public health problems. From a socio-economic perspective, PETI damages agricultural land, triggers land conflicts, and provides only short-term economic benefits that are unsustainable. Although Law No. 4 of 2009 has provided a strong legal framework, its implementation remains ineffective due to weak institutional coordination, limited monitoring capacity, and low public legal awareness. This study emphasizes the need for integrated law enforcement, broader dissemination of regulations, and the provision of sustainable economic alternatives for affected communities